Pengaruh Kelembaban Atmosfer Terhadap Visibilitas Hilal di Pantai Loang Baloq - Gazalba, Muhammad Zafanka; Sado, Arino Bemi; Sofyan, Muhammad Saleh (AL - AFAQ : Jurnal Ilmu Falak dan Astronomi, 2023)
Atmospheric humidity can affect the Rukyatul Hilal process. The greater the humidity the more difficult it is to observe the hilal, because the greater the humidity the more moisture and the more cloud growth. Therefore, the purpose of this study is to determine the level of atmospheric humidity that can affect hilal visibility at the location of Rukyatul Hilal Loang Baloq Beach. This type of research includes field research (field reseach) using a qualitative approach. The source of data from this study is the result of direct observation to the research location and collecting data from several institutions, namely, the Ministry of Religious Affairs of West Nusa Tenggara (NTB) and the Lombok Meteorology, Climatology and Geophysics Agency (BMKG). The findings of this study that atmospheric humidity affects Rukyatul Hilal on Loang Baloq Beach, because Loang Baloq Beach has a high level of atmospheric humidity. So it is difficult to observe the hilal image. If the state of atmospheric humidity is 70%, then the state of the sky will be clear. If the state of atmospheric humidity is 70% – 80% then the state of the sky will be cloudy, and if the state of atmospheric humidity is 85% then the state of the sky will rain. Atmospheric humidity at Loang Baloq Beach has an average of 84.5% throughout 2022, with this figure atmospheric humidity will be able to affect visibility on the hilal at Loang Baloq Beach.